FORMAR FORMADORES DE PROFESSORES: desafios e possibilidades - Cardoso, Dilce (2016)
In this dissertation, we reported the results of the research carried out with a group of teachers participating in the National Program for Literacy in the Right Age, who attended the training in 2014 focusing on mathematical literacy. The program was created by the Ministry of Education in 2012 and formed a partnership with the higher education institutions and the public systems of education in the country. This group is bound to the Federal University of Santa Maria, an accredited institution to provide the training. One of the objectives of the program was to ensure that all students are literate in Portuguese and Mathematics by the end of the third year of elementary school. For that to happen, a training network composed of formation teachers, linked to the higher education institutions, study mentors, chosen by their teaching systems and literacy teachers was formed. In 2013, the focus of the program was literacy and the group participating in this study was composed of 31 study mentors. The research had as main objective to investigate the work done by the formation teacher, who is also the researcher and author of the study, as well as to analyze her teaching techniques. As for the specific objectives, the understanding of mathematical concepts by the study mentors and which elements may facilitate or hinder the formation process can be pointed out. It is an investigation-training with qualitative approach. Questionnaires, interviews, mentors’ reports, the researcher's logbook, a Facebook page and two evaluative moments were used as data collection tools. In addition, the study had the epistemological support of Vygotsky’s Socio-Historical Theory (1991; 2009) and theoretical foundation in teacher training in Tardif (2012), Imbernon (2009, 2011) and Marcelo García (1999). On the formation of teachers that teach mathematics, studies by Fiorentini and Lorenzato (2012), Lorenzato (2010), Nacarato et al. (2011), Nacarato and Paiva (2013), Nunes et al (2005), Toledo and Toledo (1997; 2009) and Curi and Pires (2008), among others were used. Data analysis was based on the content analysis of Bardin (2011). From the data, it was possible to measure the performance of the formation teacher, which satisfied the study mentors with diversity of strategies and challenges, leading them to the consciousness of change in the way of teaching. The work was focused on the deconstruction and reconstruction of mathematical concepts and mechanical methods of teaching that they were experiencing from the time that the subjects surveyed were still students on elementary school. The sharing of experiences was another strong point in their formation process. The time was one of the elements that damaged the formations. Thus, more study and practices of some contents would have been needed. Noteworthy is that something that facilitated the formation was the predisposition of all advisors in the study of the issues, commitment and responsibility in learning more and more. Another element that stood out was the emergence of the formative consciousness since all of them, formation teacher and mentors, perceived to be constantly changing, constantly learning.